A Multi-Center, Randomized, Blind, Controlled Clinical Trial of the Safety and Efficacy of Micro Radio Frequency Therapy System for the Treatment of Overactive Bladder - Xu, Zhi-Hui; Zhang, Peng-Fei; Wang, Yu-Feng; Ma, Ao; Bano, Yasmeen; Ibrohimov, Alisherjon; Zhang, Chen; Jiang, Hao-Fei; Zhang, Yang; Yu, Yan-Lan; Jiang, Hai-Hong (Frontiers in Medicine, 2022)
Purpose: The purpose of this study was to evaluate the efficacy and safety of low power micro radiofrequency (RF) therapy (µRFthera®) through urethra in the treatment of overactive bladders (OAB) through a prospective, single-blind, placebo-controlled, multi-center clinical protocol. Materials and Methods: One hundred and fourteen patients with refractory OAB were randomized at 2:1 ratio, treatment to control undergoing same procedures except only the micro-RF treatment group at turned "on" setting in energy. Bladder diaries recorded during the screening period (three days before enrollment) and during follow-up period on week one, three, and seven, respectively. The patients in control could choose receiving an energized treatment during extension stage. Results: The treatment efficacy was 76.1%. There was 49.80% rate improvement compared to control (95%CL 32.48%, 67.13%). The crude rate ration (RR) was 2.89,95% CI (1.67-5.01) with p<0.001 in uni-variate analysis, while the RR became 2.94,95% CI (1.67-5.16) with p<0.001 after adjusted potential confounding factors in multi-variate analysis. Statistically significant improvements have been demonstrated in the frequency of urination, urgency, nocturia, and quality of life (QoL) scores. Conclusions: Micro RF therapy is safe and effective for the treatment of OAB. The main treatment-related complications were catheterization related complications.